Microbial community shifts in the oxic-settling-anoxic process in response to changes to sludge interchange ratio. Issue 4 (April 2019) - Karlikanovaite-Balikci, Agne; Ozbayram, E. Gozde; Yagci, Nevin; Ince, Orhan
Abstract: This particular study set out to demonstrate alterations on the microbial community of the oxic-settling-anaerobic/anoxic (OSA) process treating real domestic wastewater by changing interchange ratios (IRs). The sludge yield of systems operated at different IRs (1/13, 1/17 and 1/20) to assess sludge reduction was used to analyze microbial community composition variations. The highest IR (1/13) resulted in the highest sludge reduction (52.1%), while the OSA systems with IR of 1/17 and 1/20 reduced sludge production by 37.4% and 35.5%, respectively, in comparison to conventional systems. 16S rRNA gene amplicon sequencing analysis showed that the bacterial communities were composed of similar phylogenetic groups, Proteobacteria, Acidobacteria, and Bacteroidetes being dominant. The relative abundances differed due to the applied IRs. The highest abundance of Actinobacteria was determined at the highest IR (1/13) and increasing of the HRT to 1/20 caused a significant reduction in Actinobacteria species and the lowest abundance (6%) was determined in the OSA systems. The abundant of Thiothrix species that are boosted in the OSA trials may have a vital role in OSA systems, where its abundance was below the detection limits in the seed sludge sample. Therefore, they could be used as bioindicators in the OSA system.